Romanian Unit - Radio Free Europe/Radio Liberty Research Institute: Information Resources Department: East European Archives: Romanian Unit
Materials in this subfonds include press clippings, news agency releases, Radio Free Europe/Radio Liberty research papers and background analyses, information items, transcripts of radio broadcasts, émigré publications, and letters. The records of the Romanian Unit give a broad picture of Romanian political life, economics, culture and arts, religions, media, social and military issues. Two series of this subfonds are of outstanding interest: the Records Relating to Romanian Opposition and Protest Movement offer an encompassing and detailed overview on the history of the Romanian anticommunist opposition, dissent and dissenters; the RFE Confidential Reports on Romania consists of confidential reports from (often) anonymized, but usually reliable sources on various Romanian issues. The impressive quantity of documents on Romania’s foreign and inter-party relations, as well as those on communist propaganda included in the series Subject Files are also of great interest. Accruals not expected